Intestinal Evisceration and Hemorrhagic Shock Due to Penetrating Abdominal Trauma in Elderly Patient at Rural Area - Deny Dwi Hartanto; Dony Ruswendro (Journal of Agromedicine and Medical Sciences, 2024)
Penetrating trauma is the most frequent cause of death in patients aged 65 years and over. Penetrating trauma is often caused by armed violence, both firearms and sharp weapons, and occurs in urban civilian populations. In this case, penetrating trauma occurred in an elderly patient due to an abdominal stab wound caused by a palm sickle when harvesting palm fruit. The location of the incident was in a rural oil palm plantation area and far from the hospital. Limited facilities and resources at the community health center where the patient was first treated, resulted in initial treatment being less than optimal and inadequate. The penetrating abdominal trauma that occurred in this patient was accompanied by intestinal evisceration and hypovolemic shock which was an absolute indication for immediate laparotomy exploration. The patient's comorbidities in the form of chronic heart failure and the patient's elderly age need to be taken into consideration and attention to prevent initial and subsequent complications. After laparotomy, the patient was able to survive and recover well without any complications. Keywords: Penetrating abdominal trauma, intestinal evisceration, laparotomy